STATUS KELEMBAGAAN RADIO PEMERINTAH KABUPATEN SITUBONDO SUARA RENGGANIS - Paramitha, Amelia Ayu (Mimbar Keadilan, 2021)
AbstractThe writing entitled Institutional Status of the Situbondo District Government Radio, Suara Rengganis will discuss and discuss the first is the institutional status and the Government Radio of the Situbondo Regency Suara Rengganis until now seen from the applicable laws and regulations and the second discussion discusses the provisions regarding the institutional status of Broadcasting Institutions. Local Public (LPPL) Region based on Government Regulation which talks about the Implementation of the Broadcasting of a Public Broadcasting Institution. So that in this paper the researcher will use the normative juridical research method with the Legislative, Case and Conceptual approach. The comparative approach. Considering that local public broadcasting institutions do not yet exist in Situbondo Regency, the local government urgently needs to establish a local public broadcasting institution station to accelerate and contribute information. This research is expected to be a comprehensive research related to the institutional status of Local Public Broadcasting Institutions The local government of Situbondo Regency and of course for researchers, this research can contribute ideas for academics and of course the administrative governance of LPPL better.Keywords: broadcasting; institutional status; regional autonomyAbstrakPenulisan yang berjudul Status Kelembagaan Radio Pemerintah Kabupaten Situbondo Suara Rengganis ini akan mengupas dan membahas tentang pertama adalah status kelembagaan dan Radio Pemerintah Kabupaten Situbondo Suara Rengganis hingga saat ini dilihat dari peraturan perundang undangan yang berlaku dan pembahsan yang kedua membahas mengenai ketentuan tentang status kelembagaan Lembaga Penyiaran Publik Lokal (LPPL) Daerah berdasarkan Peraturan Pemerintah yang berbicara mengenai Penyelenggaraan tentang  Penyiaran sebuah Lembaga Penyiaran Publik. Sehingga dalam penulisan ini peneliti akan menggunakan metode penelitian yuridis normative dengan pendekatan perundang-undangan, kasus dan konseptual. Mengingat lembaga penyiaran publik lokal belum ada di Kabupaten Situbondo, pemerintah daerah setempat sangat perlu untuk mendirikan satu stasiun lembaga penyiaran publik lokal guna mempercepat dan memberikan kontribusi informasi.Penelitian ini diharapkan dapat menjadi penelitian yang komprehensif terkait dengan status kelembagaa Lembaga Penyiaran Publik Lokal dan berguna bagi Pemerintah Daerah Kabupaten Situbondo dan tentunya bagi peneliti maka penelitian ini bisa memberikan sumbangsih pemikiran bagi akademik dan tentunya tata administratif tentang LPPL dengan lebih baik.